ANALISIS POLA SEBARAN KEJADIAN LONGSORLAHAN DI KECAMATAN SOMAGEDE DENGAN SISTEM INFORMASI GEOGRAFIS - Anang Widhi Nirwansyah; M Utami; Suwarno Suwarno; Taufik Hidayatullah (Department of Urban and Regional Planning, Diponegoro University, 2015)
Landslide is part of the earth forming mechanism that is dynamic. This research is aimed at identifying the spatial pattern of landslide occurrences in Somagede District based on field survey and GIS as the tool of analysis. The survey has focused on occurrences and footprint that can be identified. Based on the field survey, there are 39 points of landslide occurrences laid in seven villages with steep and very steep slope categories. Meanwhile, the average neighbor analysis shows the clustering pattern of the landslide in Somagede, where the value of Nearest Neighbor Ratio is 0.768496. This hypothesis is supported by the z-score value of -2.77 and p-value of 0.0057 that are statistically accepted. © 2015 GJGP UNDIP. All rights reserved